Decreased glomerular filtration rate in solderers exposed to cadmium. Issue 12 (December 1995) - Järup, L; Persson, B; Elinder, C G
Abstract : OBJECTIVES–to evaluate the degree of cadmium induced glomerular impairment and to assess the dose-response relation between cadmium dose and the prevalence of glomerular dysfunction. METHODS–A comparison of glomerular filtration rates (GFR) assessed by Cr-EDTA clearance was made in 42 solderers previously exposed to cadmium for at least five years. Blood and urine data were collected at health examinations in 1984, 1989, and 1993. Individual doses of cadmium were estimated by analysing cadmium in blood. RESULTS–Glomerular lesions induced by cadmium are irreversible and the GFR decreases with the degree of tubular damage. The GFR also decreases with cadmium dose and there is a dose-response relation between blood cadmium and prevalence of glomerular damage with 3.4% prevalence at blood cadmium concentrations below 50 nmol/l, 33% at blood cadmium concentrations between 50 and 75 nmol/l and 100% prevalence of glomerular damage when cadmium in blood exceeds 75 nmol/l. CONCLUSIONS–The kidney lesions induced by cadmium are irreversible and the prevalence of those lesions are dose dependent. There is also evidence of a dose related decrease in GFR even a long time after the end of exposure. Exposure to cadmium should therefore be minimised and workers exposed to cadmium should be examined regularly for many years after the end of exposure.